Synthesis and characterization of carbazolo[2, 1-a]carbazole in thin film and single crystal field-effect transistors. Issue 28 (7th July 2017) - Más-Montoya, Miriam; Cerón-Carrasco, José Pedro; Hamao, Shino; Eguchi, Ritsuko; Kubozono, Yoshihiro; Tárraga, Alberto; Curiel, David
Abstract : Carbazole-based azaphenacene with high performance in organic field-effect transistors. Abstract : The synthesis of a hexacyclic fused polyheteroaromatic system, namely carbazolo[2, 1- a ]carbazole, via a simple two-step route is reported. Additionally, the characterization of its electronic structure is described, corresponding to a very stable molecule that is also transparent to visible light. Solid state packing is determined by X-ray diffraction analysis which, in combination with the computational calculation of the charge transfer parameters, reveals an adequate molecular arrangement to achieve a low anisotropic environment for charge transport. This π-conjugated system is used as an organic semiconductor for the fabrication of thin film and single crystal organic field-effect transistors (OFETs). Furthermore, the evaluation of different gate dielectrics results in transistors with very good hole mobilities and low operating voltages. In agreement with these results, carbazolo[2, 1- a ]carbazole becomes one of the best organic semiconductors belonging to the family of carbazole-based azaphenacenes.